Are accurate computations of the 13C' shielding feasible at the DFT level of theory? - Vila, Jorge Alberto (2014)
The goal of this study is twofold. First, to investigate the relative influence of the main structural factors affecting the computation of the 13C0 shielding, namely, the conformation of the residue itself and the next nearest-neighbor effects. Second, to determine whether calculation of the 13C0 shielding at the density functional level of theory (DFT), with an accuracy similar to that of the 13Ca shielding, is feasible with the existing computational resources. The DFT calculations, carried out for a large number of possible conformations of the tripeptide Ac-GXY-NMe, with different combinations of X and Y residues, enable us to conclude that the accurate computation of the 13C0 shielding for a given residue X depends on the: (i) (/,w) backbone torsional angles of X; (ii) side-chain conformation of X; (iii) (/,w) torsional angles of Y; and (iv) identity of residue Y. Consequently, DFT-based quantum mechanical calculations of the 13C0 shielding, with all these factors taken into account, are two orders of magnitude more CPU demanding than the computation, with similar accuracy, of the 13Ca shielding. Despite not considering the effect of the possible hydrogen bond interaction of the carbonyl oxygen, this work contributes to our general understanding of the main structural factors affecting the accurate computation of the 13C0 shielding in proteins and may spur significant progress in effort to develop new validation methods for protein structures.